The Struggle of a Person with Tourette Syndrome for Being a Teacher as Seen in “Front of The Class” Movie by Peter Werner - rose, julia; firdiansyah, firdiansyah (English Literature Department, Adab and Humanities Faculty, 2023)
This study analyze the struggle of a Person with Tourette syndrome for being a teacher in “Front of The Class” movie by Peter Werner. The aims of this research are to identify the characteristics of a Person with Tourette syndrome and the kinds of struggle used by a Person with Tourette syndrome as seen in ―Front of The Class‖ movie by Peter Werner. This research also used James Leckman et al, American Psychiatric Association and Stephen Harrison theory to find the result of the research. Researcher used descriptive qualitative method. The source of the data in this study is “Front of The Class” Movie by Peter Werner. In the data collection, the researcher used documentation technique. Then, the data were analyzed used descriptive analysis. From the results of this research, the researcher found three of physical characteristics represented of a Person with Tourette syndrome by Brad Cohen, there are the presence of tics, tics appear between 5 or 6 years of age, and repeated tics for at least one year. The researcher also found two of the mental characteristic represented by Brad Cohen, there are hard to concentrate, demonstrate disruptive behavior (impolite) and difficulty in interpersonal relationships. Then, the researcher found two kinds of struggle used by Brad Cohen, internal struggle and external struggle. Internal struggle are Brad holding tics to study, Brad tries to convince recruiter and register to be a teacher in various school. External struggle are struggle from Brad‘s family and struggle from Brad's principal (Mr. Myer).